Civil liability of breaching the obligation of depositary to maintain and return the deposit it in English law: A comparative study in Iraqi civil law - علي, يونس صلاح الدين (Journal of Legal Sciences, 2019)
The bailment is one of the well-established legal systems of the English common law, and which included the distinguished characteristics of both the law of contract and the law of property. It is worth-mentioning that this legal system has acquired those common features of these two prominent legal systems, which form an important part of the common law. By the judicial precedents made by English courts. And these precedents have adopted two different and divergent attitudes towards the qualification of the legal nature of bailment in English law . Whereas the Iraqi civil law No. (40) of 1951 regulated the legal rules of the bailment, considering it as a real contract, the conclusion of which requires the availability of four basic element. That is to say. The consent, subject-matter of the contract, cause or the motive of  contracting, and the element of delivery. But it has not adopted the notion of the sub-bailment.